The Quality of Decision-Making for School Vocational Principals: An Information System and Decision Support System Technology - Didi Supriadi; Welius Purbonuswanto (Iranian Journal of Information Processing & Management)
The principal sometimes makes decisions that cannot solve the problem because the principal does not adequately study the factors that influence and hinder the implementation of decisions before making a decision. The low quality of decisions is because of the lack of data availability or current information related to planning parameters. The unavailability of a decision support system as part of an education management information system that manages the data becomes information for school principals and is an obstacle to the quality of decision-making. The main objective of this research is proposing the decision-making model of school principals. This research is a quantitative study with a questionnaire as a research instrument. The research sample was the head of vocational schools in the Special Region of Yogyakarta and Central Java. The data analysis technique used was the analysis technique used by Structural Equation Modeling (SEM) using SmartPLS software. The results showed that the Decision Information System and the Decision Support System must support a practical decision-making quality. Both systems will have an impact on increasing alternative selection ability and analysis of problem-solving ability. Future research may develop an Android-based principal's decision support system.